Optimal demand response scheduling and voltage reinforcement in distribution grids incorporating uncertainties of energy resources, placement of energy storages, and aggregated flexible loads - Zarei, Alireza; Ghaffarzadeh, Navid; Shahnia, Farhad (Frontiers in Energy Research, 2024)
Instead of expanding power plant capacities, which is an extremely expensive investment option, demand response offers an economical solution to the challenges arising from the variability and intermittency of the renewable energy resources and demand variations, particularly during demand peak periods. This paper proposes a multi-objective optimization framework for the optimal power flow problem that integrates a stepwise demand response involving flexible and aggregated loads. The process includes short-term demand forecasting using long short-term memory (LSTM) networks in a smart distribution grid, followed by the optimal allocation of energy storage systems, and load aggregators. By determining the optimal solution point of the multi-objective problem analytically, significant system costs and peak demand can be reduced without compromising system stability. Through numerical studies for a sample study case, a reduction of 22% in system costs, 2% in total voltage variation, and 10% in peak demand is observed for a negligible impact on customers' convenience.Active Load after demand response (MW)Active Load before demand response (MW) Qi g,min /Qi g,max Minimum and maximum limits of reactive power (MVar) Qi,t L / Qi,t L0 Reactive power consumption at bus i and time t after/before demand response (MVar) Qi,t LS Reactive Load shedding in bus i at time t (MVar) Qi,t W Wind turbine reactive power generation (MVar) RUg/RDg Ramp up/down rate (MW/h) Sij,t Complex power flow from bus i to j (MVA) St Solar availability in time t (pu) SOCt State of charge of ESS at time t (MWh) Ta Ambient temperature Tin Indoor temperature of house Vi Voltage magnitude at the bus i (pu) VOLL VOLW VOLS Value of loss of load (/MWh) Value of loss of wind (/MWh) Value of loss of solar (/MWh) wt Wind availability in time t (pu) Xi,t ch,ESS / Xi,t dch,ESS Charging/Discharging power state of ESS Zij<θij Impedance of transmission line i to j (pu